Why There Should Be No Constitutional Right to Contact Counsel from a Police Car - Skolnik, Terry (Université d'Ottawa | University of Ottawa, 2015)
The Supreme Court of Canada has yet to consider whether there is a constitutional right to use a cell phone to contact legal counsel while detained in a police car. This article argues that it should not be recognized as a constitutional right for three principal reasons. First, recent judicial interpretations of the constitutional right to counsel have foreclosed the possibility of detained and arrested persons using their own cell phones to call a lawyer from a police car. Second, allowing detainees to use their cell phones to contact counsel can create unreasonable risks to public safety and undermine the privacy interests of the accused. Third, pre-existing mechanisms adequately protect the accused against self-incrimination while generating fewer risks than permitting a detainee to use her cell phone to call a lawyer. Traditional and emerging constitutional requirements related to section 10(b) of the Canadian Charter of Rights and Freedoms are satisfied by the process of the immediate transport of detained or arrested persons to a police station to contact a lawyer.
Keywords: Detention; Arrest; Procedures; Right to Counsel; Canadian Charter; the impact of technology; the collection of evidence; Public safety concerns; Privacy of arrested and detained individuals